The influence of oral antimicrobial peptide content on the quantitative microflora composition in periodontal pockets among residents of a large industrial region - Vozna, I. V.; Pavlov, S. V.; Voznyi, O. V. (Zaporozhye Medical Journal, 2021)
The aim was to study the influence of periodontal pocket microecology state on the local nonspecific resistance in steelworkers with generalized periodontitis. Materials and methods. In total, 178 patients were examined. The study group consisted of 126 patients with generalized periodontitis of initial (n = 8), I (n = 32), II (n = 68) and III (n = 18) degree of severity, chronic course, exposed to work-related hazardous agents. The comparison group consisted of 32 patients with periodontitis of initial (n = 5), I (n = 10), II (n = 11) and III (n = 6) degree of severity without exposure to harmful conditions of steel industry. The control group included 20 otherwise healthy individuals. Detection of the main five periodontopathogenic microorganisms in the crevicular fluid was carried out by the polymerase chain reaction method. The levels of lactoferrin and cathelicidin LL-37 were measured by the enzyme-linked immunosorbent assay method. Results. Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis were less common, than other opportunistic bacteria in both study groups with initial severity of generalized periodontitis. With the disease development, there was a tendency to increase the number of positive samples for all microorganisms. A correlation was found between the microorganism presence in the sample and the severity of periodontal disease. In the patients of clinical groups, the concentration of cathelicidin LL-37 in the oral fluid was reduced. In the study group, a moderate inverse correlation between cathelicidin and Porphyromonas gingivalis as well as a weak inverse correlation between cathelicidin and Prevotella intermedia were revealed. Lactoferrin was correlated directly and moderately with Porphyromonas gingivalis and Prevotella intermedia but weakly - with Treponema denticola. In the comparison group, there were a statistically significant moderate inverse correlation between cathelicidin and Porphyromonas gingivalis as well a direct correlation between lactoferrin and Porphyromonas gingivalis. Correlations between the concentrations of cathelicidin and lactoferrin in the oral fluid and other periodontopathogens were revealed to be weak. Conclusions. The studies have shown significant disruptions of the oral cavity microecology in the patients exposed to harmful effects of steel industry. The correlation between the concentration of antimicrobial peptides and periodontal pathogens in the periodontal pockets has been found.